Parasitoids of the genus Pholetesor Mason, 1981 (Hymenoptera: Braconidae: Microgastrinae) from the leafminers Lepidoptera, with the description of three new species from India - Ahmad, Zubair; Ghramh, Hamed A.; Pandey, Kavita (European Journal of Taxonomy, 2020)
Pholetesor acrocercophagus sp. nov., P. camerariae sp. nov. and P. indicus sp. nov.(Hymenoptera: Braconidae: Microgastrinae) are described as new to science. These three species were reared from Acrocercops sp., Acrocercops phaeospora Meyrick, 1916 and Cameraria virgulata Meyrick, 1914 (Lepidoptera: Gracillariidae), respectively. Characteristics of these new species and their affinities with related taxa are discussed. Data on habitat, host records and host plant species for all the parasitoid species is provided. A key to the Indian species of the genus Pholetesor Mason, 1981 reared from lepidopteran leafminers is also given.